Turbulence characteristics in the tropical mesosphere as obtained by MST radar at Gadanki (13.5° N, 79.2° E) - M. N. Sasi (Annales Geophysicae, 2001)
Turbulent kinetic energy dissipation rates (ε) and eddy diffusion coefficients (Kz) in the tropical mesosphere over Gadanki (13.5° N, 79.2° E), estimated from Doppler widths of MST radar echoes (vertical beam), observed over a 3-year period, show a seasonal variation with a dominant summer maximum. The observed seasonal variation of ε and Kz in the mesosphere is only partially consistent with that of gravity wave activity inferred from mesospheric winds and temperatures measured by rockets for a period of 9 years at Trivandrum (8.5° N, 77° E) (which shows two equinox and one summer maxima) lying close to Gadanki. The summer maximum of mesospheric ε and Kz values appears to be related to the enhanced gravity wave activity over the low-latitude Indian subcontinent during the southwest monsoon period (June – September). Both ε and Kz